Persistence of Neutralizing Antibody Responses Among Yellow Fever Virus 17D Vaccinees Living in a Nonendemic Setting - Kareko, Bettie W; Booty, Brian L; Nix, Chad D; Lyski, Zoe L; Slifka, Mark K; Amanna, Ian J; Messer, William B (The Journal of infectious diseases, 2020)
Abstract Background The once-in-a-lifetime recommendation for vaccination against yellow fever virus (YFV) has been controversial, leading to increased scrutiny of the durability of immunity after 17D vaccination. Methods This is a cross-sectional analysis of 17D vaccinees living in nonendemic Portland, Oregon. Neutralization assays were used to determine YFV immunity. The relationships between 17D immunity and vaccination history, demographics, and travel were evaluated using nominal logistic regression. Results Seventy-one of 92 (77.2%) subjects were YFV seropositive (90 percent plaque reduction neutralization test ≥1:10) at all timepoints, and 24 of 38 (63.8%) were YFV seropositive at ≥10 years after single-dose vaccination. No relationship was found between YFV immunity and time in endemic countries, other flavivirus immunity, or demographics. Subjects were most likely to become seronegative between 3 and 12 years postvaccination (logistic regression, odds ratio [OR] = 1.75; 95% confidence interval [CI], 1.12–2.73). A comparison of our results and 4 previous studies of YFV nonendemic vaccinees found that overall, 79% (95% CI, 70%–86%) of vaccinees are likely to be seropositive ≥10 years postvaccination. Conclusions These results suggest that 1 in 5 17D vaccinees will lack neutralizing antibodies at ~10 years postvaccination, and a booster vaccination should be considered for nonendemic vaccinees before travel to regions where there is a high risk of YFV transmission. Neutralizing antibody responses after single-dose vaccination with the yellow fever vaccine 17D remain high 0–3 years postvaccination but fall below a widely used neutralization threshold in a subset of vaccinees 3–12 years postvaccination.